Hybrid Enzyme‐Polymeric Capsules/Mesoporous Silica Nanodevice for In Situ Cytotoxic Agent Generation. (22nd April 2014) - Baeza, Alejandro; Guisasola, Eduardo; Torres‐Pardo, Almudena; González‐Calbet, José M.; Melen, Gustavo J.; Ramirez, Manuel; Vallet‐Regí, Maria
<x xml:space="preserve">Abstract</x> A novel nanocarrier based on functionalized mesoporous silica nanoparticles able to transport a non‐toxic pro‐drug and the enzyme responsible for its activation is presented. This nanodevice is able to generate in situ cytotoxic species once accumulated in the tumoral cell. Enzymes are sensitive macromolecules which can suffer denaturalization in biological media due to the presence of proteases or other aggressive agents. Moreover, the direct attachment of enzymes to the silica surface can reduce their activity by conformational changes or active site blockage. For these reasons, in order to create a robust system able to work in living organisms, the enzymes are previously coated with a protective polymeric shell which allows the attachment on the silica surface preserving their activity. The efficacy of this hybrid nanodevice for antitumoral purposes is tested against several human tumoral cells as neuroblastoma and leukemia showing significant efficacy. It converts this device in a promising candidate for further in vivo studies for oncology therapy.